The Contribution of Perceived Value to the Intention to Purchase Electric Motorcycles (School of Business and Management Institut Teknologi Bandung, 2022)
Abstract. Gasoline-fueled motorcycles predominate as private vehicles worldwide. The high number of motorized vehicles running on fossil fuels contributes to air pollution and hence to the destruction of the environment and of human health. This has given rise to alternative vehicles such as electric cars and motorcycles—a market which Indonesia, with its high market share of motorcycles, ought to understand better. Consumer behavior related to electric motorcycles ought to be investigated to boost adherence to this type of vehicle. This study aims to evaluate the intention of residents of Surakarta, an Indonesian city with a dynamic market, to purchase electric motorcycles. The two independent variables implemented are perceived value and age, and respondents number 184, selected through cluster sampling to represent Surakarta’s population. The study employs ordinal logistic regression, as the response variable at hand is ordinal. Results show that age and perceived value influenced the intention to purchase electric motorcycles in Surakarta. Especially based on our young and middle-aged respondents, we can conclude that as perceived value increased, so did the probability of the intention to buy an electric motorcycle.Keywords: Electric motorcycle, electric vehicle, perceived value, intention to purchase, green transportation